Analysis of the Effect of Temporal Changes on the Coolant Viscosity of the Pendinggin System on Motorcycles - Zein Muhamad; Indra Surya; Gilang Prayoga (Jurnal Indonesia Sosial Teknologi, 2024)
A combustion motor is a machine that converts from chemical energy to motion energy, where in the working system of a combustion motor produces power or engine rotation which is produced from the process of combustion in the combustion chamber (cylinder). In addition to producing power and rotation, it also produces heat (thermal) as a result of the combustion process. Excessive heat generated by the combustion process can also cause problems if not overcome properly, can cause overheating. Therefore, a good cooling system such as radiator coolant is needed, in the fluid cooling system there is viscositic (viscosity of the substance) which can affect the absorption of heat. The following are the test results at temperatures of 27.8oC (0.35dpa.s), 70oC (0.275dpa.s), 90oC (0.25dpa.s). If the viscosity value is low, then in the flow rate the faster the heat absorption and heat transfer will be more effective, while if the viscosity value is high, then in the flow rate the slower the heat absorption and heat transfer process becomes ineffective.